Social priorities and institutional arrangements for local management of the Volcánica Central-Talamanca Biological Corridor, Costa Rica - Ramírez Chávez, Jacqueline R. (Centro Agronómico Tropical de Investigación y Enseñanza (CATIE), 2014)
Tesis (M. Sc) -- CATIE, Turrrialba (Costa Rica), 2006